2014
DOI: 10.1007/s13213-014-1009-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Achromobacter sp. CX2 from symbiotic Cytophagales, a non-cellulolytic bacterium showing synergism with cellulolytic microbes by producing β-glucosidase

Abstract: A Gram-negative, obligately aerobic, noncellulolytic bacterium was isolated from the cellulolytic association of Cytophagales. It exhibits biochemical properties that are consistent with its classification in the genus Achromobacter. Phylogenetic analysis together with the phenotypic characteristics suggest that the isolate could be a novel species of the genus Achromobacter and designated as CX2 (= CGMCC 1.12675=CICC 23807). The strain CX2 is the symbiotic microbe of Cytophagales and produces β-glucosidase. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In vermicompost samples, 11.9–45.9% of the Bacteroidetes sequences were assigned to the genus Cytophagaceae_uncultured (order Cytophagales), which are cellulolytic [ 40 ]. The relative abundance of Bacteroidetes in aerobic compost samples increased with composting time from 30 d to 45 d and from 90 d to 150 d. The relative abundance of Cytophagaceae_uncultured was lower in aerobic compost (1.00–2.66%) than in vermicompost.…”
Section: Resultsmentioning
confidence: 99%
“…In vermicompost samples, 11.9–45.9% of the Bacteroidetes sequences were assigned to the genus Cytophagaceae_uncultured (order Cytophagales), which are cellulolytic [ 40 ]. The relative abundance of Bacteroidetes in aerobic compost samples increased with composting time from 30 d to 45 d and from 90 d to 150 d. The relative abundance of Cytophagaceae_uncultured was lower in aerobic compost (1.00–2.66%) than in vermicompost.…”
Section: Resultsmentioning
confidence: 99%
“…Specific mucolytic enzymes, such as glycosidase, sulfatase, and sialidase enzymes, were found in bacteria spanning several genera [41][42][43][44][45]. Strikingly, Chen et al previously isolated a novel species of Achromobacter that could produce βglucosidase [46,47], implicating the potential mechanism of A. pulmonis in mucous impairment. Genomic characterization of our A. pulmonis isolate will further help understand the mucolytic capacity of this bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…Strains of the genus Brevundimonas are opportunistic pathogens (Berg et al, 2009) and known to be involved in synergistic interactions with Anabaena and Ochrobactrum in plant growth promotion (Rana et al, 2015). Chen et al (2014) have shown the synergistic association of noncellulolytic Achromobacter sp. CX2 with cellulose-digesting Cytophagales producing β-glucosidase.…”
Section: O N L I N E C O P Ymentioning
confidence: 99%